A methodological approach to the analysis of egocentric social networks in public health research: a practical example - Djomba Janet Klara; Zaletel-Kragelj Lijana (Sciendo, 2016)
Research on social networks in public health focuses on how social structures and relationships influence health and health-related behaviour. While the sociocentric approach is used to study complete social networks, the egocentric approach is gaining popularity because of its focus on individuals, groups and communities.